Mucosal IgA responses in influenza virus infections; thoughts for vaccine design - van Riet, Elly; Ainai, Akira; Suzuki, Tadaki; Hasegawa, Hideki (Vaccine, 2012)
The current challenge in influenza vaccine design is to induce long-lasting protection not only against the vaccine strain, but also against drifted (point mutations in the surface antigens HA or NA) and even shifted (exchange of genome segments) strains. Several immune mediators that can induce cross-protection have been described, such as CD4 T-cells, CD8 T-cells and antibodies, including IgA. However, most vaccines are now administered intramuscularly or subcutaneously and subsequently relatively little is known on the role of local, mucosal responses. Since local IgA responses have been shown to play an important role in responses to natural infection, and IgA responses in mice were shown to also be involved in cross-protection, the research on mucosal influenza vaccines is currently expanding. However, the functioning of the mucosal immune system, especially in the respiratory tract, is just beginning to be revealed. Here, the current knowledge on the induction of IgA, the role of influenza specific IgA producing B-cells in anti-influenza immunity as well as the role of humoral memory responses induced upon vaccination will be reviewed.